Multimodal activity monitoring for home rehabilitation of geriatric fracture patients – feasibility and acceptance of sensor systems in the GAL-NATARS study. (September 2014) - Marschollek, Michael; Becker, Marcus; Bauer, Jürgen M.; Bente, Petra; Dasenbrock, Lena; Elbers, Katharina; Hein, Andreas; Kolb, Gerald; Künemund, Harald; Lammel-Polchau, Christopher; Meis, Markus; Meyer zu Schwabedissen, Hubertus; et al.
<x xml:space="preserve">Abstract</x> Background: Demographic change will lead to a diminishing care workforce faced with rising numbers of older persons in need of care, suggesting meaningful use of health-enabling technologies, and home monitoring in particular, to contribute to supporting both the carers and the persons in need. Objectives: We present and discuss the GAL-NATARS study design along with first results regarding technical feasibility of long-term home monitoring and acceptance of different sensor modalities. Methods: Fourteen geriatric participants with mobility-impairing fractures were recruited in three geriatric clinics. Following inpatient geriatric rehabilitation, their homes were equipped with ambient sensor components for three months. Additionally, a wearable accelerometer was employed. Technical feasibility was assessed by system and component downtimes, technology acceptance by face-to-face interviews. Results: The overall system downtime was 6%, effected by two single events, but not by software failures. Technology acceptance was rated very high by all participants at the end of the monitoring periods, and no interference with their social lives was reported. Discussion and conclusions: Home-monitoring technologies were well-accepted by our participants. The information content of the data still needs to be evaluated with regard to clinical outcome parameters as well as the effect on the quality of life before recommending large-scale implementations.